Murmurs - Sasi, Aiswarya (Research and Humanities in Medical Education, 2019)
As medical students, we tend to see patients only from the point of view of learning from them. However, patients have their own set of struggles, which we often fail to recognize. This poem explores the challenges faced by a patient in a medical college hospital, and aims to inspire empathy in the minds of medical students.